Assessment of Corticolous Lichen Diversity in Romblon State University, Main Campus, Odiongan, Romblon (Global Journal of Science Frontier Research, 2021)
Corticolous lichens grow on barks of living host trees. Their ubiquitous distribution and sensitivity to pollutants makes them ideal model organisms to biomonitor air pollution and assess air quality. But before these lichens can be used as bioindicators, it is imperative that baseline information on their diversity in a given area must be established for comparison. In this study, the diversity of the corticolous lichens was evaluated in two different sites of Romblon State University Main Campus, Odiongan, Romblon. Sampling ladders with 10 x 10 cm contiguous quadrats were used to assess the diversity of corticolous lichens from different tree species within 10 x 10 m plots set-up in the study sites. Results showed that site 2(LDV= 170.2) showed the highest lichen diversity values than site 1 (LDV= 117.9). At least nine different species of corticolous lichens were reported in this research study. Our research is one of few studies in the Philippines looking at the application of corticolous lichens in biomonitoring environmental quality.
Keywords: corticolous lichens; species diversity; bioindicator; biomonitoring